Sector specific regulation in the telecommunication market : the adoption of the 'essential facilities doctrine' as an instrument to open up the market for competition - Kubasch, Judith (Department of Commercial Law, 2016)
In almost all countries worldwide the telecommunication sector was characterized by state owned monopolies, and supplying telecommunication services was understood as a public duty. In the eighties of the last century, most countries began to liberalize their telecommunication market and try to open it up for competition. The establishment of competition in a former monopolized sector can be only successful by taking specific network related features into account. This thesis deals with the establishment of competition in the telecommunication market taking into account the so-called "essential facilities doctrine". This doctrine was developed from the U.S.American anti-trust law and is a helpful instrument to ensure access, under specific circumstances, by new competitors to facilities which are controlled by a market dominating operator.